2015
DOI: 10.4028/www.scientific.net/amm.773-774.1422
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Stiffness of Artificial Organic Soil Admixed with Lime Zeolite

Abstract: Abstract. Chemical stabilizers especially calcium based stabilizer, namely lime and cement had been widely used to modify and stabilize the soil. Extensive studies were carried out by researchers to improve the effectiveness and cost-benefit of stabilizers by introducing various types of blended lime and cement. Unconfined compressive test (UCT), one of the most simple and quick strength tests, is commonly used by researchers to indicate the suitability and successfulness of newly introduced stabilizer. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previous studies indicated that the natural zeolite could be used for improving the strength parameters and interfacial microstructure properties of cement due to pozzolanic reaction with Ca(OH) 2 because it contains of reactive SiO 2 and Al 2 O 3 [19][20][21][22][23][24][25]. However, there are few studies on the influence of natural zeolite as an additive material on the stabilized soil as environmentally friendly approaches [25][26][27][28][29][30][31]. Zeolites are microporous, hydrated aluminosilicates of alkali and alkali earth cations which commonly used as commercial adsorbents and catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that the natural zeolite could be used for improving the strength parameters and interfacial microstructure properties of cement due to pozzolanic reaction with Ca(OH) 2 because it contains of reactive SiO 2 and Al 2 O 3 [19][20][21][22][23][24][25]. However, there are few studies on the influence of natural zeolite as an additive material on the stabilized soil as environmentally friendly approaches [25][26][27][28][29][30][31]. Zeolites are microporous, hydrated aluminosilicates of alkali and alkali earth cations which commonly used as commercial adsorbents and catalysts.…”
Section: Introductionmentioning
confidence: 99%